Labor Market Integration of Young Adult Refugees in Germany: Triangulating Perspectives Toward Program Development. (July 2020) - James, Sigrid; Seidel, Franziska A.; Kilian, Juri; Trostmann, Julian
This article reports on the 18-month formative evaluation of a model project aimed at preparing young adult refugees (YARs) for entry into vocational education training (VET) as an essential step toward the labor market. Qualitative methods were used to gain insight into the perspectives of YARs, program staff, and vocational instructors as well as explore program dynamics. Within a longitudinal research design, 45 qualitative semistructured interviews were conducted with 22 of 27 program participants. Additionally, program staff and vocational instructors were interviewed. Qualitative content analysis guided the analytic process. Outcome data indicated that 83.3% of program completers or 55.6% of the program participants entered a VET within the evaluation period. Triangulated qualitative data revealed relevant program processes and generated hypotheses about factors that facilitate or hinder the difficult transition for YARs. Implications for program development as well as needed structural changes are discussed.